Coordination of AMPA receptor trafficking by Rab GTPases. (2nd November 2019) - Hausser, Angelika; Schlett, Katalin
ABSTRACT: Synaptic connections in the brain are continuously weakened or strengthened in response to changes in neuronal activity. This process, known as synaptic plasticity, is the cellular basis for learning and memory, and is thought to be altered in several neuronal disorders. An important aspect of synaptic plasticity is the tightly controlled trafficking and synaptic targeting of the AMPA-type glutamate receptors, which are the major mediators of fast excitatory transmission in the brain. This review addresses the role of Rab GTPases in AMPA receptor trafficking in neurons under basal conditions and during activity-induced synaptic plasticity, especially during long-term potentiation (LTP) and long-term depression (LTD). We highlight the importance of the tight spatio-temporal control of Rab activity and suggest that this is critical for proper neuronal functions. We also discuss how abnormal AMPA receptor trafficking and malfunctioning of Rabs can lead to neurologic disorders or memory problems.